Electrocardiogram findings of patients with serum potassium levels of nearly 10.0 mmol/L: a report of two cases. Issue 4 (19th May 2014) - Kotera, Atsushi; Irie, Hiroki; Iwashita, Shinsuke; Taniguchi, Junichi; Kasaoka, Shunji; Sagishima, Katsuyuki; Kamohara, Hidenobu; Kinoshita, Yoshihiro
<x xml:space="preserve">Abstract</x> Cases In Case 1, a 63‐year‐old woman was admitted with muscular weakness. She had hypertension, diabetes mellitus, and chronic renal failure on hemodialysis. She was taking a beta‐blocker. Her pulse rate was 42 b.p.m. (irregular rhythm); serum potassium level was 9.8 mmol/L; electrocardiogram revealed widening of the QRS complex (0.256 s). In Case 2, a 59‐year‐old man was admitted with muscular weakness. He had hypertension and chronic renal failure, and was taking a renin–angiotensin–aldosterone system inhibitor. His pulse rate was 42 b.p.m. (irregular rhythm); serum potassium level was 10.1 mmol/L; electrocardiogram revealed widening of the QRS complex (0.180 s). Outcome Life‐threatening arrhythmia did not occur, and patients survived under appropriate treatment. Conclusion Chronic renal failure, diabetes mellitus, or medications affecting extrarenal potassium homeostasis can produce a tolerance to hyperkalemia. This tolerance may help prevent life‐threatening arrhythmia despite fatal levels of serum potassium.